Recommendations on conservative therapy and secondary prevention of peripheral arterial disease (PAD): an evidence-based information brochure for sufferers - Rosenberg, Yvonne; Goertz, Hartmut; Rother, Ulrich; Uhl, Christian; Stavroulakis, Konstantinos; Pfeiffer, Manfred; Pfeiffer-Krahl, Mechtild; Behrendt, Christian-Alexander (Gefässchirurgie, 2021)
Peripheral arterial disease (PAD) is considered a common disease affecting more than 230 million people worldwide and has a bad prognosis. Owing to the systemic, progressive nature of atherosclerosis and the involvement of several vascular beds, not only is there a risk of vascular amputations but also a reduction in the general life expectancy. The thorough exhaustion of conservative therapy is considered an important pillar of complementary care, but this is not always successfully implemented. Besides structured exercise training, smoking cessation, optimisation of nutrition and body weight, antihypertensive therapy, as well as antidiabetic therapy and lipid-lowering therapy, the optimal pharmacological treatment is considered a central topic. This article is aimed at providing evidence-based recommendations for the best medical treatment for PAD in layman's terms.
CRIS-Team WoS Importer:2022-01-07